Ladontal , Griechenland: Die Begehung im Jahr 2012 - Heiden, Joachim (e-Forschungsberichte des DAI, 2023)
The settlement structures of the Ladon Valley were explored as part of the project „Olympia and its environment“. The poleis at the Ladon, one of the largest tributaries of the Alpheios in the border region between Elis and Arcadia, with their pastoral economic patterns are closely connected to the supply of the Sanctuary of Zeus in Olympia. In particular, the following cities were investigated: Thaliades and Halous at the upper Ladon, which narrows to a deep gorge there, and Thelpousa at the lower Ladon, where the wider riverbed also allowed for agriculture without elaborate terracing.